25-hydroxyvitamin D3 generates immunomodulatory plasticity in human periodontal ligament-derived mesenchymal stromal cells that is inflammatory context-dependent - Behm, Christian; Blufstein, Alice; Gahn, Johannes; Moritz, Andreas; Rausch-Fan, Xiaohui; Andrukhov, Oleh (Frontiers in Immunology, 2023)
Introduction Human periodontal ligament-derived mesenchymal stromal cells (hPDL-MSCs) exhibit a tight bi-directional interaction with CD4+ T lymphocytes. The hPDL-MSCs’ immunomodulatory abilities are drastically enhanced by pro-inflammatory cytokines via boosting the expression of various immunomediators. 25-hydroxyvitamin D3 (25(OH)D3), the major metabolite of vitamin D3 in the blood, affects both hPDL-MSCs and CD4+ T lymphocytes, but its influence on their interaction is unknown. Methods Therefore, primary hPDL-MSCs were stimulated in vitro with tumor necrosis factor (TNF)-α a or interleukin (IL)-1β in the absence and presence of 25(OH)D3 followed by an indirect co-culture with phytohemagglutinin-activated CD4+ T lymphocytes. The CD4+ T lymphocyte proliferation, viability, and cytokine secretion were analyzed. Additionally, the expression of various immunomediators in hPDL-MSCs was investigated, and their implication was verified by using pharmacological inhibitors. Results 25(OH)D3 significantly counteracted the suppressive effects of IL-1β-treated hPDL-MSCs on CD4+ T lymphocyte proliferation, whereas no effects were observed in the presence of TNF-α. Additionally, 25(OH)D3 significantly increased the percentage of viable CD4+ T lymphocytes via TNF-α- or IL-1β-treated hPDL-MSCs. It also caused a significant decrease in interferon-γ, IL-17A, and transforming growth factor-β productions, which were triggered by TNF-α-treated hPDL-MSCs. 25(OH)D3 significantly decreased the production of various immunomediators in hPDL-MSCs. Inhibition of two of them, prostaglandin E2 and indoleamine-2,3-dioxygenase-1, partially abolished some of the hPDL-MSCs-mediated effects of 25(OH)D3 on CD4+ T lymphocytes. Conclusion These data indicate that 25(OH)D3 influences the immunomodulatory activities of hPDL-MSCs. This modulatory potential seems to have high plasticity depending on the local cytokine conditions and may be involved in regulating periodontal tissue inflammatory processes.